Student Perceptions of Guidance and Counseling Services at SMKN 1 Grati - Siti Wulandari(; Taqiyyatunnisa’ Maulidy Azanabilah; Wardatuz Zahro’ul Mukaromah (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Abstract. This study aims to describe students' perceptions of guidance and counseling (BK) services at SMKN 1 Grati. The study used a qualitative descriptive approach, with data collection techniques including observation, interviews, and questionnaires. The results indicate that most students understand the function of BK services as a means of helping students overcome academic, personal, social, and career problems and supporting the development of their potential. Students' perceptions of the quality of BK services were generally positive, as demonstrated by assessments of the BK teachers' friendly demeanor, good communication skills, confidentiality of services, and willingness to provide solutions tailored to students' needs. These perceptions are influenced by various factors, such as personal experience, communication with BK teachers, the school environment, peer influence, service programs, available facilities, and students' level of understanding of BK's function. Furthermore, students expect improved service quality through easier access to consultations, the development of career guidance programs, the use of digital technology, improved counseling facilities, and strengthening the relationship between BK teachers and students. Therefore, BK services at SMKN 1 Grati play a crucial role in supporting student development and need to be continuously improved to optimally meet student needs.